Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_535_540
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior in Monocrystalline Ni-Based Superalloys for Blade Applications

Abstract: Ni-based superalloys are used for turbine airfoil applications due to their excellent high temperature properties. Alloy design has historically focused on creep resistance as the critical design limiting parameter. Recently, the focus has shifted to include fatigue resistance, resulting in the need to better understand the effects of alloy microstructure on fatigue crack initiation and propagation. In this study, sustained peak low cycle fatigue tests of coated monocrystalline René N5 specimens oriented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…The failure crack progression on (001) is much deeper than the total thickness of the coating and interdiffusion layers, which is about 100 lm. Similar fracture surfaces were observed after compressive dwell fatigue tests at 1253 to 1373 K (980 to 1100°C), [7] and the features are consistent with those observed at high temperature and low frequency. [1] At lower temperatures, cracks initiate and propagate on {111} crystallographic plane along deformation twins.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The failure crack progression on (001) is much deeper than the total thickness of the coating and interdiffusion layers, which is about 100 lm. Similar fracture surfaces were observed after compressive dwell fatigue tests at 1253 to 1373 K (980 to 1100°C), [7] and the features are consistent with those observed at high temperature and low frequency. [1] At lower temperatures, cracks initiate and propagate on {111} crystallographic plane along deformation twins.…”
Section: Resultssupporting
confidence: 86%
“…The deformation behavior depends on temperature, frequency, and environment. [1][2][3][4][5][6][7][8] It has been reported that creep deformation plays a significant role at higher temperatures, above about 1223 K (950°C), due to the large amount of the stress relaxation during the hold. At lower temperatures, formation of shear bands and twinning after crack initiation causes the failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yablinsky and colleagues [10] have reportedly observed similar discontinuous p-type rafts in René N5 single crystals tested under zero-compression dwell fatigue at 1100°C. It has been established from previous studies that the formation of p-type rafts occurs in alloys with a negative -' misfit, when subjected to a compressive stress applied along [001].…”
Section: Discussionmentioning
confidence: 87%
“…Rafting of the -' microstructure has been primarily studied under constant load creep conditions [13][14][15]. Rafting can also occur under TMF loading conditions [16] or during strain-controlled isothermal fatigue tests incorporating tensile or compressive dwell periods [10]. Progressive ' coarsening, whether directional or isotropic in nature, can result in significant changes in the cyclic stress-strain response of the material and hence the fatigue failure mechanism [17].…”
Section: Introductionmentioning
confidence: 99%